Anti-Rheumatoid Arthritis Activity of 96% Ethanol Extract of Eleutherine bulbosa Bulbs with Arthritis Induction Adjuvant Method - Muthia, Rahmi; Wati, Helmina; Jamaludin, Wahyudin Bin; Kartini, Kartini; Setiawan, Finna; Zanirah, Gina Rizki (Borneo Journal of Pharmacy, 2023)
An autoimmune condition known as rheumatoid arthritis (RA) results in chronic joint inflammation. Side effects that occur during long-term RA treatment are dangerous. Therefore, many people prefer herbal medicines, estimated to have lower side effects; one such herb is bawang dayak (Eleutherine bulbosa Urb.) bulbs. This study aimed to determine the class of compounds and the effective dose of the 96% ethanol extract of E. bulbosa bulbs, which had an anti-RA effect in the Wistar strain with the Adjuvant Induced Arthritis (AIA) model. Eleutherine bulbosa bulb extract was macerated with 96% ethanol. In the tests with extract doses of 100, 200, and 400 mg/KgBW and methylprednisolone 15 mg/KgBW, the induction used Complete Freund's Adjuvant (CFA). Treatment was provided from day eight through 21 of the test's 21-day duration. Phytochemical screening results contain alkaloids, flavonoids, phenols, quinones, saponins, steroids, and tannins. The percentage inhibition of edema volume and joint thickness, respectively, extract doses of 100, 200, 400 mg/KgBW, and methylprednisolone 15 mg/KgBW were 27.9585%, 49.3446%, 53.3239%, and 58.4629%; as well as 64.9809%, 73.8022%, 74.1444%, and 74.1825%. After analyzing the results, it was determined that E. bulbosa bulb extracts in 96% ethanol can treat RA at effective 200 and 400 mg/KgBW (p-value <0.05).